Water Balance Analysis and Design of Water Resources Conservation in Prumpung Watershed, Tuban District, East Java - Muhammad Syahdan Shah; Muhammad Yanuar Jarwadi Purwanto (Jurnal Teknik Sipil dan Lingkungan, 2016)
Development of the region will increase water requirement. Increased water use will influence human intervention on water resources. The purpose of this study were to analyze water availability and water demand, and to provide recommendation of conservation to increase water storage capacity in Prumpung basin, Tuban. Prumpung basin geographically located between three sub-districts: Bancar, Kerek and Tambakboyo with an area of 22.319,14 ha. The calculation was conducted using water balance analysis. The total water requirement in Prumpung watershed in 2014 was 138.295.090,73 m3/year and water availability was 64.157.428 m3/year. It meaned that in 2014 Prumpung watershed had water deficit of 74.137.662 m3/year and need water conservation program. Conservation programs were conducted by using artificial well, rorak terrace, and retention pond. The number of conservation unit required were 53.281 units artificial wells, 1.077.708 units rorak terrace, and 72 units retention ponds which can absorb water of 142.665.013 m3/year. Total cost required was Rp 516.823.553.224,00.Keywords: conservation design, water availability, water balance,water deficit, water  requirements